Integrating Character-based Thematic Learning Activities to Promote Early Child' Character Acquisition - Somantri, Annie Susany (Universitas Negeri Semarang, 2019)
The important role of character education in the child's psychological development is continually promoted as early as possible. By integrating the characters in accordance with the varied learning materials, the role of children in acquiring the character's values will be much better promoted. Integrating character-based thematic learning activities is one of the models in providing critical environment in the children’s development. Therefore, this study aims to 1) analyze the needs of character-based teaching materials model for early childhood in West Java, 2) design a character-based thematic learning model to help the acquisition of character values, and 3) validate the proposed model. The method used is research and development. In this study, there were three early child education studies in West Java selected based on the accreditation of BAN PNF of West Java region and for model validation, the two experts were involved to evaluate the activities provided and the model itself. Related to the needs of character-based learning activities, the schools still need variations in the learning process that integrates the characters. The current models used in the schools are in need to be enhanced for better effects on the children. In addition, in this model, the validation results indicate that this model meets aspects of the teaching materials approach and objectives, publicity, and content design, with minor improvements in the characteristics of instructional learning media and evaluation. The activities offered in the model may provide, to some extent, the flexibility for the teacher to adapt the children’s different character acquisition.